2023
DOI: 10.1590/1677-5449.202300122
|View full text |Cite
|
Sign up to set email alerts
|

Clinically important left superior polar artery giving rise to a left inferior suprarenal artery and an aberrant left inferior polar artery: a case report

Abstract: The renal arteries arise from the lateral side of the abdominal aorta at the L2 vertebral level, just below the origin of the superior mesenteric artery. Multiple aberrant renal arteries can pose difficulties in renal transplantation, interventional radiological and urological procedures, renal artery embolization, angioplasty, or vascular reconstruction for congenital and acquired lesions. We present a case of a left kidney supplied by the left renal artery along with superior and inferior polar arteries, ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…An APRA may be a direct branch of the aorta or it may arise from any of the visceral branches of the aorta located in the vicinity. In 2023, Kumar et al 8 described a unique case wherein three arteries were observed supplying the left kidney, two of which were superior and inferior polar arteries, arising from the aorta and the inferior mesenteric artery respectively. In addition to these, the superior polar artery further sprouted a left inferior suprarenal artery.…”
Section: Discussionmentioning
confidence: 99%
“…An APRA may be a direct branch of the aorta or it may arise from any of the visceral branches of the aorta located in the vicinity. In 2023, Kumar et al 8 described a unique case wherein three arteries were observed supplying the left kidney, two of which were superior and inferior polar arteries, arising from the aorta and the inferior mesenteric artery respectively. In addition to these, the superior polar artery further sprouted a left inferior suprarenal artery.…”
Section: Discussionmentioning
confidence: 99%